Peran TPI (Tempat Pelelangan Ikan) Terhadap Tingkat Perekonomian Berbasis Kerakyatan Pada Masyarakat Nelayan (Studi di Desa Batu Nampar Selatan).: The Role of TPI (Fish Auction Place) in the Level of People-Based Economy in the Fishing Community in South Batu Nampar Village - Muhamad Zaril Gapari (Al-Faizi : Jurnal Politik, Hukum dan Bisnis, 2025)
The potential for development based on marine and fisheries resources which is the economic domain of the Department of Maritime Affairs and Fisheries is the utilization of capture and aquaculture fisheries resources, both marine and public waters, fisheries processing industry, marine and freshwater biotechnology, valuable objects and management of small islands. The purpose of this study is to determine the role of TPI and the extent of TPI's influence in contributing to the economic level of the fishing community in Batu Nampar Selatan Village. This study is a qualitative study with a descriptive method. Data collection uses observation, structured and unstructured interviews, and documentation. The respondents are TPI Managers, Entrepreneurs, Retailers, and Fishermen. Data analysis uses inductive analysis. Based on the findings of data in the field, it can be reported that the results of the study include: (1) The mechanism of management and sale of fish at TPI (Fish Auction Place), namely TPI Batu Nampar Selatan is managed by UPTD (Regional Technical Management Unit). UPTD appoints a leader and 6 staff who are tasked with carrying out activities at TPI. The method of selling fish at TPI is by auctioning by an auctioneer so that it can benefit both parties, both sellers and buyers. And (2) The role of TPI (Fish Auction Place) in the level of the people-based economy in the fishing community in Batu Nampar Selatan Village, can be said to have played a role in accommodating fishermen's catches, assisting in auctions, maintaining price stability, and increasing regional income as well as improving the fishermen's economy, as evidenced by the decreasing levels of poverty and unemployment and the high level of education.